Synthesis of nanocrystalline tetragonal zirconia by a polymeric organometallic method - Quinelato, A. L.; Longo, Elson [UNESP]; Leite, E. R.; Varela, José Arana [UNESP] (Wiley-Blackwell, 1999)
A polymeric precursor method based on the Pechini process was successfully used to synthesize zirconia-12 mol% ceria ceramic powders, the influence of the main process variables (citric acid-ethylene glycol ratio, citric acid-total oxides ratio and calcination temperature) on phase formation and powder morphology (surface area and crystallite size) were investigated. The thermal decomposition behavior of the precursor is presented. X-ray diffraction (XRD) patterns of powders revealed a crystalline tetragonal zirconia single-phase, with crystallite diameter ranging from 6 to 15 nm. The BET surface areas were relatively high, reaching 95 m(2) g(-1) Nitrogen adsorption/desorption on the powders suggested that nonaggregated powders could be attained, depending on the synthesis conditions. Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: Pechini process; zirconia; ceramic; x-ray diffraction